Biomarker Distributions as Maturity Indicators in Coals, Coaly Shales, and Shales From Taiwan - Jun-Chin Shen Wuu-Liang Huang (Terrestrial, Atmospheric and Oceanic Sciences, 2007)

(untitled)
The distribution of hopanoids and alkanes in bitumen extracts of coals, coaly shales, and shales from northwestern Taiwan has been measured to assess the maturity of potential petroleum source rocks in the studied area. The C31 homohopane isomers of the studied coals and coaly shales attain equilibrium at maturity corresponding to 0.6% Ro measured in coals or 0.65% Ro in adjacent shales. A proposed parameter using hopanoid ratios reveals a more consistent trend and approaches a steady value at maturity similar to the C31 homohopane isomer ratio. The results show that the onset of the main phase of petroleum generation in northwestern Taiwan takes place at maturity corresponding to VR of 0.6% Ro measured in coals or coaly shales and probably higher VR in shales. The distribution of pristane, phytane n-C17 and n-C18 confirms the validity of the conventional maturity indicators if the samples are from the same source, but shows depositionalor organic-source controls. The source influence on the phytane/n-C18 ratio appears to be larger than that on the pristane/n-C17 ratio. The phytane/n-C18 ratio is also less sensitive to maturity than that of the pristane/n-C17 ratio. The pristane/phytane ratios in the studied coals and coaly shales, in contrast to the pristane/n-C17 ratio, continue to decrease to maturities beyond the oil window up to 1.5% Ro and therefore may be applicable to high maturity sources.